Pre-Treatment of Empty Oil Palm Bunches (EOPB) Using Autoclave with Variations in H2SO4 Solvent Concentration to Increase Cellulose Content - Ganing, Melani; Suleman, Annisa Inayah; Putri, Suriati Eka; Diana, Sri; Syafaatullah, Achmad Qodim (Fakultas Teknologi Industri - Universitas Muslim Indonesia, 2024)
Empty Oil Palm Bunches (EOPB) are waste products from palm oil mills, the waste is produced in large quantities, but most palm oil mills have not utilized this waste product adequately. There are several contents of EOPB, namely cellulose, hemicellulose and lignin, each of which has economic value so that it can be utilized further. One significant opportunity is that cellulose in EOPB will be converted into glucose or bioethanol. Bioethanol is one of the options in supporting the availability of renewable energy resources. The bioethanol production process consists of initial pretreatment, hydrolysis, fermentation and purification. The delignification process of Empty Oil Palm Bunches (EOPB) using physical and chemical pretreatment can break down lignin and hemicellulose so that cellulose can be converted into glucose in bioethanol production. The pretreatment procedure with H2SO4 solvent is used to increase cellulose content. The purpose of this study was to determine how different concentrations of H2SO4 affect the amount of cellulose in the EOPB pretreatment process. Additional studies on bioethanol can be done with this cellulose content. There is an experimental component in this study, namely through direct observation and testing of materials containing different concentrations of H2SO4, namely 3%, 5%, and 7%, data were collected through laboratory experiments. The cellulose content for 0% H2SO4 concentration was 16.15%, 3% H2SO4 was 30.00%, 5% H2SO4 was 36.35%, and 7% H2SO4 was 41.09% indicating that the H2SO4 solvent can increase the cellulose content.